2023
DOI: 10.1186/s12886-023-02934-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of keratoconus (including oxidative stress biomarkers) in a cohort study of Shiraz university of medical science employees in Iran

Abstract: Background To determine the prevalence of keratoconus in Shiraz University of Medical Sciences Employees and the related risk factors including oxidative stress biomarkers. Methods 2546 subjects’ mean age ± SD, 40.35 ± 6.70 (46% male) were recruited. All participants underwent objective refraction using auto-refractometer and retinoscopy, followed by subjective refraction, and bio-microscopy. Pentacam imaging was performed for the detected keratoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A case‒controlled multicenter study in a Turkish population found that the mean BMI values in both the KC and control groups were within normal ranges [ 15 ]. No significant difference was found between KC and non-KC subjects in an Iran study [ 17 ]. Slater JA et al [ 23 ] reported a ratio of 5% KC in 60 obese patients awaiting bariatric surgery, with a 100-fold increased prevalence compared with the overall population (0.05%), although the difference was not statistically significant due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case‒controlled multicenter study in a Turkish population found that the mean BMI values in both the KC and control groups were within normal ranges [ 15 ]. No significant difference was found between KC and non-KC subjects in an Iran study [ 17 ]. Slater JA et al [ 23 ] reported a ratio of 5% KC in 60 obese patients awaiting bariatric surgery, with a 100-fold increased prevalence compared with the overall population (0.05%), although the difference was not statistically significant due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, several limited studies have been conducted to explore the relationship between BMI and KC. Although several studies have failed to confirm that BMI is a risk factor for KC [ 15 , 17 ], a nationwide study suggested an strong independent association between BMI and KC [ 9 ]. Furthermore, there is still a lack of evidence on the interactive effect of eye rubbing and BMI on KC, which are all closely related to the expression of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the impact of high BMI on keratoconus remains unclear. Past reports have indicated that in Australian patients ( 11 ), a higher BMI was not associated with an increased risk of keratoconus; a recent study in Iran ( 12 ) found no significant difference in BMI between keratoconus patients and control subjects. However, recent findings suggest that a high BMI may be a risk factor for keratoconus.…”
Section: Introductionmentioning
confidence: 87%